The Semantic Role of Actor and Object Clauses in Sentences in Crime News Texts - Nantu, Marselina Yosefina; Rustono, Rustono; Mardikantoro, Hari Bakti (Universitas Negeri Semarang, 2023)
Actor and object clauses are clauses whose elements have syntactic roles as actors and occupy syntactic functions as objects. The elements that form clauses with actors and objects in crime news texts have certain semantic roles. This study aims to determine the semantic role of clauses with actors and objects in sentences in crime news texts. This research is qualitative research. The data in this research is in the form of sentences that allegedly contain clauses with actors and objects. The data collection method used in this research is listening to method with tapping technique as the basic technique and note-taking technique as the advanced technique. The data analysis method used in this research is agih method. The analysis techniques used in this research are direct element dividing technique, sentence constituent analysis technique, lesap technique, expansion technique, change of intent technique, mark reading technique, and extrapolation technique. The method of presenting the results of data analysis used in this research is formal and informal methods. The result of this research is the semantic role of clauses with actors and objects in sentences in crime news texts are eleven, namely (1) actors, (2) actions, (3) targets, (4) benefactor, (5) tools, (6) time, (7) participant, (8) ways, (9) sources, (10) places, and (11) results.